2023
DOI: 10.1021/acsami.2c19526
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cancer Nanovaccine to Induce Antigen-specific Immune Responses Based on Large-Sized Porous Silica Nanoparticles

Abstract: Cancer vaccine is one of the immunotherapeutic strategies aiming to effectively deliver cancer antigens to professional antigen-presenting cells such as dendritic cells (DCs), macrophages, and B cells to elicit a cancer-specific immune response. Despite the advantages of the cancer vaccine that can be applied to various cancer types, the clinical approach is limited due to the non-specific or adverse immune responses, stability, and safety issues. In this study, we report an injectable nanovaccine platform bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To enhance mRNA delivery efficiency while minimizing systemic biodistribution, we developed large-sized rigid nanoparticles, L-PPSNs. To prepare L-PPSNs, we first synthesized large-sized bare PSNs following our previous report with a slight modification. , The synthesis involved the use of cetyltrimethylammonium bromide (CTAB) as a template to create a porous structure and tetramethyl orthosilicate (TMOS) as the silica precursor. Subsequently, we applied PEI (1.8 kDa) through electrostatic interaction to facilitate the mRNA loading and delivery .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To enhance mRNA delivery efficiency while minimizing systemic biodistribution, we developed large-sized rigid nanoparticles, L-PPSNs. To prepare L-PPSNs, we first synthesized large-sized bare PSNs following our previous report with a slight modification. , The synthesis involved the use of cetyltrimethylammonium bromide (CTAB) as a template to create a porous structure and tetramethyl orthosilicate (TMOS) as the silica precursor. Subsequently, we applied PEI (1.8 kDa) through electrostatic interaction to facilitate the mRNA loading and delivery .…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles were received from Lemonex Inc. L-PPSNs were synthesized according to the previously published method with slight modification. , In brief, CTAB and 1 M NaOH solution were dissolved in methanol/water (0.6/0.4 = w/w). With vigorous stirring, TMOS was added under ambient conditions, and the mixture was aged overnight after 8 h of stirring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PSN is an appropriate vehicle for carrying KYNase mainly due to its flexible surface chemistry, pore size control, and biocompatibility . Furthermore, PSNs can be degraded into oligomers or monomers in the body fluid and excreted through renal clearance. , In the previous study from our group, the protein-loaded PSNs showed an increased retention time in the TME compared to free protein. , Inspired by the result, we designed a type of PSN suitable for carrying KYNase, named ‘BALL’ First, the pore size of BALL was chosen at ∼12 nm to load KYNase, whose hydrodynamic size is known to be around 9 nm . Next, the pore surface of BALL was designed to present a positive charge under physiological conditions, leading to an electrostatically attractive interaction with KYNase, whose isoelectric point is smaller than 7.0.…”
Section: Introductionmentioning
confidence: 99%